Podróże powtórzone (Dmitrij Bykow, „Uniewinnienie”, „Sygnały”) - Zywert, Aleksandra (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The present paper aims at analyzing two novels by Dmitry Bykov: Justification(1998) and Signals (2013). On the basis of both their subject and formal representation we may state that they may be considered a dilogy. In the former the author focused on a specific problem — an alternative version of the causes, course and consequences of Stalinist repressions. The latter touches upon the issue of the existing reality anddetermination to attain goals in the context of a contemporary Russian’s mentality,which is largely affected by Soviet thinking